Mobile Health Technology to Improve Care for Patients With Atrial Fibrillation - Guo, Yutao; Lane, Deirdre A; Wang, Limin; Zhang, Hui; Wang, Hao; Zhang, Wei; Wen, Jing; Xing, Yunli; Wu, Fang; Xia, Yunlong; Liu, Tong; Wu, Fan; et al. (Journal of the American College of Cardiology, 2020)
Current management of patients with atrial fibrillation (AF) is limited by low detection of AF, non-adherence to guidelines, and lack of consideration of patients' preferences, thus highlighting the need for a more holistic and integrated approach to AF management. The objective of this study was to determine whether a mobile health (mHealth) technology-supported AF integrated management strategy would reduce AF-related adverse events, compared with usual care. This is a cluster randomized trial of patients with AF older than 18 years of age who were enrolled in 40 cities in China. Recruitment began on June 1, 2018 and follow-up ended on August 16, 2019. Patients with AF were randomized to receive usual care, or integrated care based on a mobile AF Application (mAFA) incorporating the ABC (Atrial Fibrillation Better Care) Pathway: A, Avoid stroke; B, Better symptom management; and C, Cardiovascular and other comorbidity risk reduction. The primary composite outcome was a composite of stroke/thromboembolism, all-cause death, and rehospitalization. Rehospitalization alone was a secondary outcome. Cardiovascular events were assessed using Cox proportional hazard modeling after adjusting for baseline risk. There were 1,646 patients allocated to mAFA intervention (mean age, 67.0 years; 38.0% female) with mean follow-up of 262 days, whereas 1,678 patients were allocated to usual care (mean age, 70.0 years; 38.0% female) with mean follow-up of 291 days. Rates of the composite outcome of 'ischemic stroke/systemic thromboembolism, death, and rehospitalization' were lower with the mAFA intervention compared with usual care (1.9% vs. 6.0%; hazard ratio [HR]: 0.39; 95% confidence interval [CI]: 0.22 to 0.67; p < 0.001). Rates of rehospitalization were lower with the mAFA intervention (1.2% vs. 4.5%; HR: 0.32; 95% CI: 0.17 to 0.60; p < 0.001). Subgroup analyses by sex, age, AF type, risk score, and comorbidities demonstrated consistently lower HRs for the composite outcome for patients receiving the mAFA intervention compared with usual care (all p < 0.05). An integrated care approach to holistic AF care, supported by mHealth technology, reduces the risks of rehospitalization and clinical adverse events. (Mobile Health [mHealth] technology integrating atrial fibrillation screening and ABC management approach trial; ChiCTR-OOC-17014138).